Anatomical Location of the Segmental Spinal Arteries in the Cervical Intervertebral Foramina: 3D-Micro CT Findings Relevant to Transforaminal Epidural Injection - Jun B; Yang HM; Shin DA; Jung HH; Cho TH; Kim SH (Journal of Pain Research)
Byongnam Jun,1 Hun-Mu Yang,2– 4 Dong Ah Shin,5 Hyun Ho Jung,5 Tae-Hyeon Cho,3,6,* Shin Hyung Kim1,3,* 1Department of Anesthesiology and Pain Medicine, Yonsei University College of Medicine, Seoul, Republic of Korea; 2Translational Laboratory for Clinical Anatomy, Department of Anatomy, Yonsei University College of Medicine, Seoul, Republic of Korea; 3Translational Research Unit for Anatomy and Analgesia, Seoul, Republic of Korea; 4Surgical of Anatomy Education Centre, Yonsei University College of Medicine, Seoul, Republic of Korea; 5Department of Neurosurgery, Yonsei University College of Medicine, Seoul, Republic of Korea; 6Department of Anatomy, College of Korean Medicine, Semyung University, Jecheon, Republic of Korea*These authors contributed equally to this workCorrespondence: Tae-Hyeon Cho, Department of Anatomy, College of Korean Medicine, Semyung University, Semyung-ro 65, Jecheon-si, Chungcheongbuk-do, 27136, Republic of Korea, Tel +82-43-649-1348, Fax +82-43-649-1348, Email gods176@semyung.ac.kr Shin Hyung Kim, Department of Anesthesiology and Pain Medicine, Yonsei University College of Medicine, 50-1 Yonsei-ro Seodaemun-gu, Seoul, 03722, Republic of Korea, Tel +82-2-2228-7500, Fax +82-2-364-2951, Email tessar@yuhs.acPurpose: Cervical transforaminal epidural steroid injection (TFESI) is a common treatment for cervical radiculopathy but carries potential risks because of the presence of crucial arteries in the intervertebral foramina (IVF). This study analyzed the precise anatomical location of the segmental spinal artery (SSA) within the cervical IVF using 3D micro-CT imaging to provide guidance for safer TFESI procedures.Participants and Methods: Fourteen embalmed cadavers were used in this study: three for serial sectional dissection, two for histological examination, and nine for micro-CT analysis. Each IVF was divided into quadrants (ASQ, antero-superior quadrant; PSQ, postero-superior quadrant; AIQ, antero-inferior quadrant; PIQ, postero-inferior quadrant) for detailed measurements of SSA locations, comparing dimensions and spatial relationships among C4– 5, C5– 6, and C6– 7 levels.Results: Forty-four IVFs were analyzed by micro-CT, and the results revealed that SSAs were predominantly located in the ASQ (36 of 44 cases, 82%) and PSQ (8 of 44 cases, 18%) of the IVF. No SSAs were observed in the AIQ and PIQ. Significant dimensions and shapes were consistent across individuals, with cervical IVF increasing in size from C4– 5 to C6– 7.Conclusion: Together, these findings demonstrated the predominance of SSAs in the ASQ, emphasizing the need for precise anatomical guidance during TFESI to avoid vascular injury. In addition, the cervical spine exhibits anatomical variability, indicating that greater caution is required when treating the cervical spine compared with the lumbar spine and highlighting the importance of targeting the PIQ to avoid the SSA and other vascular structures.Keywords: cervical transforaminal epidural steroid injection, micro-computed tomography, segmental spinal artery